IMPLEMENTASI PROGRAM ENGLISH DAY UNTUK MENINGKATKAN SKILL SISWA DI SD IT TAHFIZ AN-NUR KELURAHAN PANGKALAN LESUNG - Azmi, Zul; Lady, Triana; Marisa, Cily Tria; Rahman, Abdul; Hertianti, Elsa (Komunitas Manajemen Kompetitif, 2023)
Abstract: This community service aims to increase students' literacy in English. The implementation of the English day program at SD IT Tahfiz An-nur, Pangkalan Lesung Village, was carried out as a habituation technique by motivating and familiarizing with language practice. The methods used in implementing the English day program are the lecture method, discussion method, cooperative learning method, and project based. The results show that there is an increase in enthusiasm and students' ability to pronounce words, connect sentences and vocabulary in students. The results of observations using test indicators show an increase in students' ability in English at the elementary school level. The results show a positive response and will make English day activities a continuous routine program at school. Keywords: Motivation, Language practice, English day, Interest in Learning